BELANJA MODAL DITINJAU DARI DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH KABUPATEN DAN KOTA DI PROVINSI BALI TAHUN 2016-2020 - Ni Putu Vira Cintya Dewi; Tiara Kusuma Dewi; Gde Herry Sugiarto Asana (Universitas Triatma Mulya, 2023)
Local governments utilize their capital expenditure budgets to construct facilities and infrastructure for the development of their respective regions. The distribution of capital expenditure is influenced by various factors, including local original revenue and balancing funds. The objective of this research is to examine the impact of local original income and balancing funds on capital expenditure in the regencies and cities of Bali. The data for this study was collected through the documentation method, gathering, processing, and recording data from secondary sources relevant to the research. The study population comprises the Regency and City Governments of Bali, which consist of eight districts. The results indicate that the profit sharing fund has a positive effect on capital expenditure. It is recommended that local governments in Bali focus on further developing potential sources of regional income to enhance their Regional Original Revenue (PAD). This can be achieved through the intensification of tax collection and the formulation of regional regulations that support economic activities within the regions. The allocation of balancing funds such as General Allocation Fund (DAU), Specific Allocation Fund (DAK), and Special Allocation Fund (DBH) should prioritize areas that directly impact public interests, such as infrastructure and facilities that stimulate economic growth. It is important to avoid diverting the balancing fund and PAD for non-beneficial expenditure allocations. Capital expenditure should be carried out with the aim of providing optimal public services and generating income for the region..